ChemInform Abstract: Buckled Germanene Formation on Pt(111). Issue 40 (30th September 2014) - Li, Linfei; Lu, Shuang‐zan; Pan, Jinbo; Qin, Zhihui; Wang, Yu‐qi; Wang, Yeliang; Cao, Geng‐yu; Du, Shixuan; Gao, Hong‐Jun
Abstract Germanene, a one‐atom‐thick Ge layer with a honeycomb structure is prepared in an ultra‐high vacuum system by deposition of Ge on Pt(111) at room temperature followed by annealing at 600—750 K for 30 min.